Post-release GPS tracking of hand-reared Irish hare Lepus timidus hibernicus leverets, Slemish, Co. Antrim, Northern Ireland - Reid, Neil; Harrison, Alan T. (2011)
Animal rescue centers release large numbers of captive-bred, rehabilitated, or translocated animals into the wild annually but little is known about their post-release survival and behavior. We developed a novel and innovative coupling of traditional radio-tags with new GPS loggers to track hand-reared Irish hare Lepus timidus hibernicus leverets after release into the wild. Cyanoacrylate SuperGlue ® proved a poor fixative, with two out of three leverets managing to detach their tags within 24 hr. Nevertheless, a total of 2,505 GPS locations were recorded every 60 sec for one leveret over three nights (approx. 835 per night). The leveret dispersed <410 m from the original release site. It demonstrated exploratory behavior, including an ability to navigate accurately in a complex and unfamiliar environment, returning to a habitual lie-up site each day. Its survival was confirmed up to 9 days post-release at which time its radio-tag detached; however, similarly aged leverets were sighted in the area for up to 2 mo post-release (suggesting possible longer-term survival). This is the first study to publish data from any GPS-tagged lagomorph and provides 'proof-of-concept' that large quantities of behavioral data can be recovered from small mammals 1-2 kg. Further development of these techniques will be highly valuable to future studies.